Una técnica sencilla de distalización de caninos retenidos - Mariaca-de Botero, Libbe; Botero-Mariaca, Paola (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Diagnosis and early treatment of impacted canines is necessary to avoid future complications that will harm dental arch integrity. Early traction of the canine involves its distalization when it is located high in the vestibule with a mesial inclination. The use of removable appliance is recommended in order to avoid secondary ejfects in the adjacent teeth. This type of therapy can be the only one or can be a first slage of a complex treatment depending upon patient needs.